Online brand community and consumer brand trust: Analysis from Czech millennials - John Amoah; Abdul Bashiru Jibril; Sulemana Bankuoru Egala; Solomon A. Keelson (Cogent Business & Management, 2022)
To ensure effective and efficient relationship marketing, brand management has become an asset (pre-requisite) for quality service marketing to thrive. Brands have gone viral to develop communities to interact with existing and novice consumers. However, the relationships between these online communities and brand trust are less explored in the literature, given the fact that consumers and users of information are core beneficiaries of these communities. The study, hence, adopted a referral (snowball) method of sampling technique to identify and gather data from social media users who are mainly millennials from the Czech Republic. Five hypotheses were tested using PLS-SEM with 534 valid respondents. The results show that online brand community has a direct significant effect on consumer's brand trust, and indirect significant via the mediating role of peer-to-peer interaction and consumer brand engagement. Hence, the research provides managers (brand practitioners) with new insights regarding the motivations (brand promise and trust) as consequence of interacting in online brand communities. Again, this study enhances social media marketing and branding literature for researchers and practitioners to leverage on the relevance of online brand community for a firm's competitive edge. Limitation and future research directions are considered.
Keywords: 650; consumer brand engagement; consumer brand promise & trust; Czech Republic; millennials; online brand community; peer-to-peer interaction